Impact of GST in E – Commerce Industry: The India Prospect (Trinity Journal of Management, IT & Media (TJMITM), 2018)
The power of digital distribution over physical retail outlets is you  have a chance to create a global audience. This is exactly what  the E-Commerce Industry is trying to capitalize, and they have  been extremely successful in it. Name anything, and you get it at  your doorstep with one click. Also, the E-Commerce industry has  been aptly utilizing the consumer behaviour pattern, for example  by providing discounts to expand their horizons. Has the  introduction of GSTaffected the empire of E-Commerce?
Keywords: GST; GSTIN